Do Selective COX-2 Inhibitors Affect Pain Control and Healing After Arthroscopic Rotator Cuff Repair? A Preliminary Study. Issue 3 (March 2018) - Oh, Joo Han; Seo, Hyuk Jun; Lee, Ye-Hyun; Choi, Hye-Yeon; Joung, Ho Yun; Kim, Sae Hoon
Background: Selective cyclooxygenase (COX)–2 inhibitors are commonly used analgesics that provide similar analgesia as that of other analgesics but with fewer adverse effects. However, few prospective studies have performed comparative analyses in this regard. Purpose: To evaluate the efficacy of a selective COX-2 inhibitor in early postoperative pain control, satisfaction with pain management, and incidence of systemic adverse effects in patients undergoing arthroscopic rotator cuff repair. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This study included 180 patients who underwent arthroscopic rotator cuff repair between September 2011 and August 2012. The patients were randomly assigned to receive celecoxib, ibuprofen, or tramadol (n = 60 each). Visual analog scale (VAS) scores for pain intensity and satisfaction with medication, incidence of adverse effects, and use of rescue medication were recorded and compared between the 3 groups at 3 days and 2 weeks after surgery. Magnetic resonance and ultrasonography images of 82 patients were retrospectively reviewed at least 24 months after surgery, along with the range of motion and pain VAS and functional scores. Results: There were no significant differences among the 3 groups in terms of pain intensity, incidence of adverse effects, or dosage of rescue medication at 3 days or 2 weeks after surgery. Pain VAS and functional scores at the final follow-up were also comparable among the 3 groups. However, the retear rate in the celecoxib group (11/30 [37%]) was significantly higher than those in the ibuprofen (2/27 [7%]) and tramadol (1/25 [4%]) groups ( P = .009). Conclusion: Despite having similar postoperative analgesic effects as other nonsteroidal anti-inflammatory drugs and opioids, selective COX-2 inhibitors should not be used for postoperative analgesia because they might negatively affect tendon-to-bone healing after surgical repair. Registration: NCT02850211 (ClinicalTrials.gov identifier)